2019
DOI: 10.3390/safety5010009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Food Safety Knowledge and Practices among Foodservice Staff in Al Madinah Hospitals, Saudi Arabia

Abstract: This study examines food safety knowledge and practices of food service staff in Al Madinah hospitals, Saudi Arabia. A total of 163 food service staff participated voluntarily from 10 hospitals across the city of Al Madinah. The participants completed a questionnaire composed of three parts: General characteristics, food safety knowledge, and food safety practices. Results showed that respondents generally had good food safety knowledge with the highest pass rate of 77.9% for knowledge of cross contamination f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
48
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 42 publications
17
48
2
Order By: Relevance
“…This finding is consistent with the studies conducted by Abdul-Mutalib et al. (2012) , Alqurashi et al. (2019) , Farrish et al.…”
Section: Resultssupporting
confidence: 94%
“…This finding is consistent with the studies conducted by Abdul-Mutalib et al. (2012) , Alqurashi et al. (2019) , Farrish et al.…”
Section: Resultssupporting
confidence: 94%
“…(2012) , age and experience did not seem to have significant effects on the findings. There are also some studies that have found no significant association of gender and marital status with food safety knowledge of food handlers ( Taha et al., 2020 ; Alqurashi et al., 2019 ; Carbas et al., 2013 ; Gruenfeldova et al., 2019 ; Kunadu et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…1132 practice based on difference in gender in some previous studies. 6,[43][44][45][46][47] This might be due to other factors such as educational status and work role which could predict the food safety practice better than gender.…”
Section: Dovepressmentioning
confidence: 99%